PHYSICAL BODY RISKS DURING PURSE SEINE FISHING EQUIPMENT OPERATION ON KM. GODBLESS 08 - Ikhsan, Suci Asrina; Arkham, Muhammad Nur; Haris, Rangga Bayu Kusuma; Kelana, Perdana Putra; Maulana, Muhammad Agung (Aurelia Journal, 2024)
Work productivity can decrease if a worker suffers from musculoskeletal disorders (MSDs). Ergonomic review study so that MSDs can be prevented or minimized. The study examined MSDs in ABK operating purse seine fishing gear. The method used in this study is the WERA (Workplace Ergonomic Risk Assessment) method. The results of the study obtained the risk level in 3 work positions with a medium level and one work position at a low level. The score at the medium level is between 39 and 42 scores, while the score for the low level itself is at 27. The highest score is in the stern work position with a value of 42 and the lowest score occurs in the work position handling the catch with a value of 27.